Adsorptive removal of Safranine T dye from aqueous solutions using sodium alginate-Festuca arundinacea seeds bio-composite microbeads - Karadeniz, Sabri Can; Isik, Birol; Ugraskan, Volkan; Cakar, Fatih (ELSEVIER, 2023)
In this study, composite microbeads were prepared using Festuca arundinacea seeds and sodium alginate biopolymer at different ratios and utilized as sorbents for the sorption of Safranine T from wastewater. The sorbents were characterized by FTIR, SEM, XRD, and BET analysis. According to BET analysis, the specific surface area of the adsorbents was calculated to be 10.99 m2/g and the surface was found to be mesoporous. The optimum conditions for adsorption studies including initial pH (2-12), concentration (10-50 mg/L), contact time (0-150 min), and adsorbent mass (0.05 g/50 mL-0.25 g/50 mL) were determined at 25 degrees C. The raw data obtained from sorption tests were applied to Freundlich, Langmuir-1, Langmuir-2, Langmuir-3, Langmuir-4, Temkin, Toth, and Koble-Corrigan isotherm models. The best results were obtained from the Langmuir-2 and accordingly the qm values were calculated as 454.54, 833.33, and 625.00 mg/g for FA, FA-SA-20, and FA-SA-30 at 25 degrees C, respectively. Adsorption kinetic data illustrated that the process followed the PSO model. Reusability and desorption studies were performed for composite microbeads. Additionally, the thermodynamic studies were performed at 25, 35 and 45 degrees C. Considering all these results, it was seen that the FA-SA-20 composite had the highest adsorption capacity and the best desorption efficiency.
Keywords: Adsorption -desorption; Sodium alginate; Festuca arundinacea seeds; Safranine T; EQUILIBRIUM ISOTHERM; ACTIVATED CARBON; SURFACE-AREA; WASTE-WATER; KINETICS; ADSORBENT; BEADS; PERFORMANCE; LANGMUIR; THERMODYNAMICS; Biochemistry & Molecular Biology; Chemistry; Polymer Science